Development of a ducted horizontal axis marine current turbine rotor - Abdul Aziz, Azliza (2010)
Marine current energy resource has great potential to be exploited on a large scale because of its predictability and intensity. This energy can be extracted by various kinds of device, one of which is Horizontal Axis Marine Current Turbine (HAMCT). This thesis describes the development of a HAMCT to extract marine current energy suitable for Malaysian sea. The marine current speed in the Malaysian sea is quite low, averaging only about 1 m/s (2.0 knots). Presently available HAMCT designs are not suitable for low current speeds since a large turbine is needed while the blade diameter is limited to water depth. In this thesis, the problem is circumvented by placing the rotor in a duct, which helps to increase the water speed. The HAMCT rotor and duct were developed using Computer Aided Design (CAD) technique and analysed using Computational Fluids Dynamics (CFD) software. For the rotor, simulations were carried out with two conditions; ‘without duct’ and ‘with duct’. A 4.884 m diameter rotor with various numbers of blade and design tip speed ratio (TSR) were developed. The duct was developed in two different shapes, in which each shape has 5 variations of cylinder length. From the simulation of ducts, the current speed at the entrance of the cylinder is taken into account because the rotor is placed inside the cylinder. Thus, the maximum current speed generated was used in the ‘with duct’ simulation condition, while ‘without duct’ condition is when the rotor is simulated using actual current speed. The output power and performance of rotor are investigated using two methods; CFD simulation results and Blade Element Momentum (BEM) theory. It was found that the rotor model 4B2 is the greatest rotor because of its highest power coefficient for both methodst. The output power of the ducted turbine was significantly enhanced compared to the one without duct, which is 546.931W and 4250.012W by BEM. Validation was carried out by comparison to Batten work and it shows that the shapes of curves for both works are similar which this is sufficient to validate that the results of this project are genuine and acceptable.